Health Effects of Alternate Day Fasting Versus Pair-Fed Caloric Restriction in Diet-Induced Obese C57Bl/6J Male Mice - Henderson, Chloe G.; Turner, Damian L.; Swoap, Steven J. (Frontiers in Physiology, 2021)
Alternate day fasting (ADF) induces weight loss and improves various markers of health in rodents and humans. However, it is unclear whether the benefits of ADF are derived from the lower caloric intake of ADF or from the 24-hour fasting period. Therefore, this study directly compared selected markers for health – such as glucose control, body weight, liver triglycerides, T cell frequencies, and others – in high-fat (60% calories from fat) diet-induced obese mice subjected to either ADF or caloric restriction (CR). Obese mice were then randomly assigned to one of four groups: 1) ADF: remained on the high-fat diet, but fed on alternate days (n=5) PF: remained on the high-fat diet, but pair-fed to the ADF group (n=5), 3) LF: moved to a chow ad libitum diet (n=5; 17% calories from fat), and 4) HF: remained on the high-fat ad libitum diet (n=5). An additional group of non-obese mice maintained on a chow diet since weaning were used as controls (CON: n=5). After 10 weeks, ADF, PF, and LF mice ate fewer kcals, had a lower body mass, had smaller epididymal fat pads, improved glucose tolerance, and had a lower hepatic triglyceride content relative to HF mice (p<0.05), but none reached that of CON mice in these measures. T cell frequencies of the spleen, blood, and mesenteric lymph nodes were reduced in ADF, PF, and HF compared to the CON group. Importantly, there were no significant differences between the ADF and PF groups in any of the measurements made in the current study. These data suggest that ADF, PF, and LF diets each lead to improved markers of health relative to high-fat diet-induced obese mice, and that the caloric restriction associated with ADF is the major factor for the noted improvements.